Invisible search and online search engines the ubiquity of search in everyday life - Haider, Jutta (Routledge, 2019)
Invisible Search and Online Search Engines considers the use of search engines in contemporary everyday life and the challenges this poses for media and information literacy. Looking for mediated information is mostly done online and arbitrated by the various tools and devices that people carry with them on a daily basis. Because of this, search engines have a significant impact on the structure of our lives, and personal and public memories. Haider and Sundin consider what this means for society, whilst also uniting research on information retrieval with research on how people actually look for and encounter information. Search engines are now one of society's key infrastructures for knowing and becoming informed. While their use is dispersed across myriads of social practices, where they have acquired close to naturalised positions, they are commercially and technically centralised. Arguing that search, searching, and search engines have become so widely used that we have stopped noticing them, Haider and Sundin consider what it means to be so reliant on this all-encompassing and increasingly invisible information infrastructure. Invisible Search and Online Search Engines is the first book to approach search and search engines from a perspective that combines insights from the technical expertise of information science research with a social science and humanities approach. As such, the book should be essential reading for academics, researchers, and students working on and studying information science, library and information science (LIS), media studies, journalism, digital cultures, and educational sciences.